Risk factors for nasal bleeding in patients undergoing transnasal gastrointestinal endoscopy. Issue 5 (12th January 2018) - Mieda, Mitsuyo; Miyashita, Hiroshi; Osawa, Hiroyuki; Hirasawa, Tomosuke; Makino, Nobuko; Toma, Sachiko; Tomiyama, Takeshi; Miura, Yoshimasa; Lefor, Alan K.; Yamamoto, Hironori
Abstract: Transnasal endoscopy is widely used in screening for upper gastrointestinal lesions because of less associated pain. Nasal bleeding is the most severe adverse effect, but specific risk factors have not been identified. The aim of this study is to identify risk factors for nasal bleeding during transnasal endoscopy. Nasal bleeding occurred in 160/3035 (5.3%) of patients undergoing transnasal endoscopy as part of health checkups. Patient data were retrospectively evaluated including anthropometric, medical, and life‐style parameters with multiple logistic regression analysis. Multiple logistic regression revealed that nasal bleeding was significantly associated with age in decades [odds ratio/10 years 0.78, 95% confidence interval (CI) 0.63–0.97, p  = 0.027], female gender (2.15, 95% CI 1.48–3.12, p  < 0.001), a history of previous upper gastrointestinal endoscopy (0.55, 95% CI 0.36–0.82, p  = 0.004), and chronic/allergic rhinitis (0.60, 95% CI 0.36–0.98, p  = 0.043). Other factors including the use of antiplatelet and/or anticoagulant drugs were not significantly associated with nasal bleeding. Female and young patients are significantly associated with an increased risk of bleeding from transnasal endoscopy, but antiplatelet and/or anticoagulant medications and a history of chronic/allergic rhinitis may not be associated.